Lattice-based interpenetrating phase composite metamaterial fabricated with hybrid material extrusion process for tunable mechanical properties - Ritik Raj; Jung-Ting Tsai; Mayur Jiyalal Prajapati; Jeng-Ywan Jeng (Journal of Materials Research and Technology)
Interpenetrating phase composite (IPC) is a unique type of material that may exhibit tunable mechanical and functional properties. This study introduces a novel hybrid material extrusion (MEX) technique to fabricate lattice-based IPC metamaterials. This approach aims to functionally tune mechanical properties by incorporating diverse material phases within the lattice voids. Two different designs—sea urchin (SU) and hybrid (H) lattice were 3D printed using thermoplastic polyurethane (TPU) as the outer material. The lattice voids were filled with combinations of polyamide (PA)-12 powder, 316L stainless steel-based slurry, and polyurethane (PU) foam, resulting in three IPC configurations (IPC- type I: foam-powder-powder, IPC- type II: foam-slurry-powder, and IPC- type III: foam-slurry-slurry). Comprehensive static and dynamic compression tests were conducted to evaluate the mechanical properties of the resulting IPC metamaterials. Hybrid lattice-based IPC metamaterials demonstrated superior mechanical properties compared to their SU counterparts. IPC-type I demonstrated a substantial improvement in mechanical performance, exhibiting a compressive strength up to 5 times higher and an energy absorption per unit volume up to 2.5 times greater than empty or single-phase metamaterials. Under dynamic conditions, both designs showed distinct properties in hysteresis work, tan δ, and dynamic elastic recovery (DER). The study also explores the effects of varying loading rates and frequencies on the IPC metamaterials' mechanical behavior. Overall, this study presents an innovative fabrication technique for IPC metamaterials, revealing how the strategic placement and stacking sequence of secondary materials within the primary structure significantly influences their mechanical properties.